Alleviation of cadmium phytotoxicity in triacontanol treated Coriandrum sativum L. by modulation of physiochemical attributes, oxidative stress biomarkers and antioxidative system. (May 2022) - Sardar, Rehana; Ahmed, Shakil; Akbar, Muhammad; Yasin, Nasim Ahmad; Li, Guihua
Abstract: Cadmium (Cd) is a hazardous metal that has a significant risk of transfer from soil to edible parts of food crops including shoots and seeds. Reduction of Cd accumulation is required to lower the risk of Cd exposure in humans and animals feeding on metal contaminated parts of such plants. Coriandrum sativum L. (coriander) exposed to Cd showed stress symptoms such as stunted growth, reduced photosynthetic activity and synthesis of chlorophyll pigments. Growth inhibition in Cd-treated plants was attributed to induction of oxidative stress as demonstrated by higher level of stress biomarkers such as electrolyte leakage, lipid peroxidation and hydrogen peroxide. Primary objective of the current study was to observe the ameliorative role of triacontanol (Tria) in Cd-stressed coriander seedlings. For this purpose, coriander seeds were primed with Tria concentrations of 5, 10, and 20 μmol L −1 . Seedlings developed from Tria treated seeds exhibited reduced loss of photosynthetic pigments; mitigated oxidative stress caused by Cd, through improved efficacy of antioxidant machinery comprising superoxide dismutase (SOD), peroxidase (POX), and catalase (CAT) enzymes besides non-enzymatic antioxidants including proline, phenolics and flavonoids. Triacontanol treated seedlings showed enhanced yield attributes suggesting that exogenous Tria could be employed to improve plant tolerance to Cd stress. Graphical abstract: Image 1 Highlights: Cadmium stress declined seed germination and subsequent growth of Coriandrum sativum seedlings. Seed priming with triacontanol mitigated Cd toxicity in C. sativum. Triacontanol improved antioxidant potential, photosynthetic activity and growth of plants. Triacontanol reduced Cd uptake in treated seedlings.